Do World Product Mandates Really Matter? - Feinberg, Susan E. (Journal of International Business Studies, 2000)
This paper examines whether MNC subsidiaries with world product mandates fared better than non-specialized subsidiaries in the face of Canada-U.S. trade liberalization. Using confidential affiliate-level panel data on 445 Canadian subsidiaries of U.S. MNCs, empirical analysis finds that affiliates with higher levels of R&D and human capital resources grew relatively more when trade was liberalized. However, R&D- and human-capital-intensive affiliates experienced systematically different growth patterns. The findings imply that world product mandates do reduce affiliates' vulnerability to downsizing, and that human capital development and R&D may be equally important in building world product mandates.